The history of King Lear - Shakespeare, William, 1564-1616 (Shakespeare, William, 1564-1616. Works. 1982., 2008)
The introduction illminates the plays' origins and practicalities of composition, its reception and influence. Detailed notes pay special attention to language and staging, and the volume includes King Lear's first derivative, a contemporary ballad, and guides to appreciation of the play and its multiple offshoots.